2021
DOI: 10.1071/an19597
|View full text |Cite
|
Sign up to set email alerts
|

Forage value of vegetative leaf and stem biomass fractions of selected grasses indigenous to African rangelands

Abstract: Context. Rangeland grasses native to Africa constitute the main diet for free-ranging livestock and wild herbivores. Leaf:stem ratio is a key characteristic used for assessing quality of forages. However, studies to determine the allocation of biomass to leaves and stems as well as chemical components and nutritive value, especially of grasses in African rangelands, are rare.Aim. This study was conducted to establish biomass allocation and chemical and mineral components in leaf and stem fractions of three gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Generally, the leaf is more digestible, higher in CP and lower in fiber components than the stems [ 39 ]. Such differences in feed nutrition between the leaf and the stem might be attributed to the photosynthesis/metabolic role of leaves and the structural role of stems [ 40 ]. Consequently, improving feed quality relies, at least partially, on increasing the proportion of the leaf when harvested.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the leaf is more digestible, higher in CP and lower in fiber components than the stems [ 39 ]. Such differences in feed nutrition between the leaf and the stem might be attributed to the photosynthesis/metabolic role of leaves and the structural role of stems [ 40 ]. Consequently, improving feed quality relies, at least partially, on increasing the proportion of the leaf when harvested.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, however, all genotypes showed higher values of DMD in leaf blades than stems for the three cuts evaluated. Mganga et al 49 . found similar results in Eragrostis superba , Enteropogon macrostachyus , and Cenchrus ciliaris .…”
Section: Discussionmentioning
confidence: 62%
“…In our work, however, all genotypes showed higher values of DMD in leaf blades than stems for the three cuts evaluated. Mganga et al 49 found similar results in Eragrostis superba, Enteropogon macrostachyus, and Cenchrus ciliaris. However, it is noteworthy that Mutale and Vencedor genotypes had higher digestibility values in the earlier stages for stems, but not at the level of leaf blades.…”
Section: Discussionmentioning
confidence: 64%
“…Urochloa humidicola cv. Llanero showed the highest leaf:stem ratio, which influences the quality of the forage and improves grazing efficiency when above 1 (Grev et al, 2020;Mganga et al, 2021). Among the Megathyrsus cultivars evaluated, the higher stem weight seen in cv.…”
Section: Resultsmentioning
confidence: 98%